Annual Report of the Society for Financial Studies for 2018–2019 - Ellul, Andrew; Goldstein, Itay; Holden, Craig; Masulis, Ron; Pontiff, Jeffrey; Schoar, Antoinette (The Review of Corporate Finance Studies, 2020)
The Society for Financial Studies (SFS) is a global, nonprofit academic society in finance. It owns and runs three academic journals: (1) the Review of Asset Pricing Studies, (2) the Review of Corporate Finance Studies, and (3) the Review of Financial Studies. It also organizes two annual academic conferences: (1) the SFS Cavalcade Asia-Pacific and (2) the SFS Cavalcade North America. It also runs several smaller, specialized conferences and financially supports and co-sponsors other independent conferences. Its governing board is the SFS Council. SFS holds an annual membership meeting in May every year. At that meeting the SFS President, Executive Editors, Cavalcade Chair, and Secretary-Treasurer report on SFS activities. This year, for the first time, we have written up those reports and integrated them into this annual report of the Society for Financial Studies, which will be published in all three SFS journals. The reasons for doing this are to share this information more broadly with SFS members and friends and to create a permanent record for the long run (that is, institutional memory).